The use of project-based learning methods in physics - Murzagalieva Ә.Г.; Г.; Aubakir І.Е. (Recent Contributions to Physics, 2025)
This article examines the effectiveness of project-based learning in a high school physics course using the example of studying the interference of mechanical waves. The research work was conducted with the aim of modernizing the content of physics teaching in the era of digital transformation, basing the learning process on scientific and practical activities, and developing students’ research skills. Project-based learning in physics increases students’ research activity and allows them to connect their theoretical knowledge with practical experience. The article analyzes the theoretical and methodological foundations of the project approach and identifies its advantages in mastering scientific knowledge. During the study, students a small project studying the interference of mechanical waves. The project stages included proposing a hypothesis, creating an experimental setup, observing, collecting data, and analyzing the results. The experimental results showed that changes in wave frequency and amplitude affect the structure of the interference pattern. The obtained data were matched with theoretical models and confirmed the correctness of physical laws. The project results showed that the project-based learning method significantly develops students’ research, analytical and communicative competencies. According to the survey results, the majority of students noted that project work increased their interest in the subject, cognitive activity and ability to work together. The study proves that project-based learning is an effective pedagogical model for teaching physics in the context of digital transformation and the importance of introducing it into the updated content of general education.